2014
DOI: 10.1007/s11172-014-0756-7
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocenes as potential anticancer drugs. Facts and hypotheses

Abstract: We analyzed the research data on antitumor effects of a wide range of ferrocene compounds and discussed possible mechanisms of their bioactivities. Current trends in the study of antican cer effects of ferrocene derivatives were considered. Promising ways in the design of low toxicity anticancer ferrocene based drugs of new generation were outlined. * Dedicated to the 60th anniversary of the A. N. Nesmeyanov Institute of Organoelement Compounds of the Russian Academy of Sciences (INEOS RAS). The review was wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 123 publications
0
41
0
Order By: Relevance
“…Antitumor activity of ferrocene compounds is presently under active investigations, and the authors have also succeeded in this field . However, at the moment there are only a few publications on the effects of the ferrocene‐substituted compounds on the brain .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Antitumor activity of ferrocene compounds is presently under active investigations, and the authors have also succeeded in this field . However, at the moment there are only a few publications on the effects of the ferrocene‐substituted compounds on the brain .…”
Section: Resultsmentioning
confidence: 99%
“…During the first two decades of the 21st century, special attention was paid to the synthesis and bioassay of ferrocene derivatives carrying pharmacophoric groups, namely, nucleic bases, oligonucleotides, various heterocycles, amino acids, peptides, and sugars . In vitro and in vivo studies have demonstrated that many of such modified ferrocenes display a wide spectrum of biological activities, including antianemic, antimicrobial, antibacterial, antimalarial, tuberculostatic, and especially antitumor activities, see recent review articles . Ferroceron (tetrahydrate of sodium salt of ortho ‐carboxybenzoyl ferrocene), which is the first and only currently ferrocene‐based drug, has been effectively used for a long time for the treatment of iron deficiency pathologies .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[1] Ferrocenylheterocyclic compounds have been found to exhibit a wide range of biological activities (e.g. antitumor [2,3] and antimicrobial [4] ). Ferrocene containing porphyrins have already been synthesized by various synthetic methods.…”
mentioning
confidence: 99%